(untitled) (SAARC Journal of Agriculture, 2016)
A field experiment was conducted during 2012-13 and 2013-14 crop season to find out the most effective strategies for management of late blight of potato. It was observed that prophylactic spray with mancozeb @ 0.2% followed by fenamidone + manozeb @ 0.3% as 2nd spray at the onset of the disease followed by mancozeb @ 0.2% as 3rd spray seven days after application of the 2nd spray followed by one more spray with fenamidone+mancozeb @ 0.3% as 4th spray seven days after application of 3rd spray exhibited best management of late blight of potato in terms of percent reduction of disease over control which was 83.64 and 84.79% in 2012-13 and 2013-14 crop season, respectively. The total tuber yield was also highest in this treatment showing 25.84 and 26.78 t ha-1 during 2012-13 and 2013-14 crop season, respectively. SAARC J. Agri., 14(1): 111-117 (2016)